Business strategy engineering (BSE): um método proposto para planejamento estratégico da inovação em startups - Medeiros, Gilvandro César de (2023)
Startups are flexible and innovative organizations that seek to adapt their business models to gain competitive advantages and establish themselves in the market. In the corporate world, strategic planning has been presented as a solution for companies' top management to structure their business models, aligning the objectives of the company's management vision with the processes and activities carried out by each department and team. However, startups face difficulties in applying strategic management methods due to a range of factors, including the uncertainties arising from the business model under construction and the need to act in an agile manner to contemplate the frequent changes that are part of these companies' routines. In this context, the goal of this research is to explore the fundamentals of strategic planning and associated methodologies, relating them to the limitations and needs of startups, in order to propose a useful approach for entrepreneurs to adopt strategic planning in their organizations. For this purpose, a reinterpretation and analysis of the literature on strategic management and strategic planning methods were presented, addressing the fundamentals of competitive advantage, strategic inflection theory, principles of antifragility applied to business, and the issues that interfere with the success of startups, proposing a combination of the Balanced Scorecard (BSC) and Objectives & Key-Results (OKRs) models for the strategic management of these organizations. With this focus, the Business Strategy Engineering (BSE) approach combines these concepts and organizes them in a flexible and agile manner, adapting to the reality of startups. As a result, applications of BSE are discussed and exemplified, and a guiding manual is suggested for the application of BSE as a tool to assist in the development of strategic planning in an innovation-oriented business model.